Phytochemical, brine shrimp lethality assay, antibacterial and antioxidant activity screening of Nypa fruticans ("Nipa") leaf extracts - Lavilla, Charlie A. Jr (Asia-Pacific Journal of Science, Mathematics, and Engineering, 2015)
The present study was designed to evaluate the phytochemicals, cytotoxicity and antioxidant activites of Nypa fruticans extracts. Phytochemical screening revealed presence of flavonoids, alkaloids, phlobatannins, saponins, and steroids. the ethyl acetate extract at 1000ppm showed bioactivity against nauplii artemia salina. The extracts showed no inhibition against B. subtilis and E. coli. Furthermore, the antioxidant activity of the extracts weretested by its ability to reduce Mo (VI) to Mo (v) through subsequent formation of green phosphate Mo(V)-complex at acidic pH and positive results were observed in ethyl acetate extracts and fractions as indicated by their ascorbic acid equivalents.